2021
DOI: 10.3390/ijerph18041805
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Networking Sites and Pro-Environmental Behaviors: A Mediation and Moderation Model

Abstract: Climate change poses a huge threat. Social networking sites (SNSs) have become sources of human–environment interactions and shaped the societal perception of climate change and its effect on society. This study, based on the extended parallel process model, aims to examine the effect of exposure to climate change-related information on SNSs on the pro-environmental behaviors of individuals. The study examines the mediation effect of fear of victimization from climate change between the exposure to climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 131 publications
2
12
0
1
Order By: Relevance
“…A study on green consumer disposition towards patronising green hotels in Taiwan indicated that PBC significantly mediates the association between individuals' environmental concerns and environmental‐friendly behaviour (Chen & Tung, 2014). In addition, Shah et al (2021)) found a significant mediating role of fear of victimisation between exposure to climate change‐related information and pro‐environmental behaviour among large universities in China. The fear of victimisation is conceptualised as the control behaviour in which an individual perceives threat as a motivation to implement a behaviour (Nabi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study on green consumer disposition towards patronising green hotels in Taiwan indicated that PBC significantly mediates the association between individuals' environmental concerns and environmental‐friendly behaviour (Chen & Tung, 2014). In addition, Shah et al (2021)) found a significant mediating role of fear of victimisation between exposure to climate change‐related information and pro‐environmental behaviour among large universities in China. The fear of victimisation is conceptualised as the control behaviour in which an individual perceives threat as a motivation to implement a behaviour (Nabi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang and Skoric (2018) analysed the role of media consumption in shaping citizens’ environmental behaviours finding that social media might encourage environmental consumerism among nonmembers of Environmental Non-Governmental Organisations. Shah et al, (2021) suggest that exposure to climate change-related information on social media positively influences users’ pro-environmental behaviours. However, this literature focuses on the exposure to media content rather than on the concrete use of Internet technologies to limit the physical impact that individuals have on the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The social capital discussed in this study refers to the social capital of community residents, which is analyzed in five dimensions: social network, social trust, social norms, sense of community belonging, and community voluntarism. Firstly, social network refers to a kind of “local social relationship network”, which is an individual social network that includes neighborhood relationships and interactions formed by community residents via community participation [ 43 ]. Secondly, social trust refers to a special trust relationship formed by the community residents in the process of long-term interaction [ 17 ].…”
Section: Methodsmentioning
confidence: 99%